3D circuit model for 3D IC reliability study - Tan, Cher Ming (2010)
3D integrated circuit technology is an emerging technology for the near future, and has received tremendous attention in the semiconductor community. With the 3D integrated circuit, the temperature and thermo-mechanical stress in the various parts of the IC are highly dependent on the surrounding materials and their materials properties, including their thermal conductivities, thermal expansivities, Young modulus, poisson ratio etc. Also, the architectural of the 3D IC will